The Influence of Leadership, Motivation and Discipline on Organizational Commitment and Its Impact on Employee Performance at the Agriculture Office in Pidie Regency - Zulkifli, Zulkifli; Italina, Cut (Institute of Computer Science (IOCS), 2020)
The purpose of this research was to determine the influence of empirical evidence of the leadership, motivation and discipline toward organization commitment. All of these were effected to the employee performance at the government duty of agriculture of Pidie district. The data used were primer and secondary from 125 respondents. Structural Equation Modeling (SEM) was used as the data analysis method and helped by AMOS 21. The result showed that the leadership, motivation and discipline variable had a positive impact toward organization commitment. They also had positive influence toward the employee performance. While the variable of mediation testing showed that organization commitment mediated the correlation among leadership, motivation and discipline fully toward the employee of the government duty of agriculture in Pidie District Area.